The rules for kings (Majlis Aceh) - Jusoh, Yahaya (Penerbit UTM, 2008)
This book is an English translation of the manuscript of Majlis Aceh, originally called “Ma Bayyana al–Salatin” which means Rules for Kings. The manuscript was written in its complete form by Ismail bin Ahmad in 1231 A.H/1815 A.D). It is an Important document on the development of the rules and civilization of the Muslim Malay Society in Southeast Asia, particularly in Aceh. The manuscript consists of rules and regulations for kings and officers and their responsibilities, enforcement and details the amount of custom duties and taxes for trading goods and services in Aceh. All the royal customs and rules of governance exhibit the influence of tradition (adat) and Islamic teaching. The manuscript also shows the great influence of Islam in trade and commerce. The Rules for Kings (Majlis Aceh) would be beneficial to readers, researchers and academicians in the field of history, education, sociology, politics, literature, law and civilization of the Malay Islamic world in Southeast Asia.